Literasi Keuangan Digital di Lingkungan Pedagang UNLA dalam Penggunaan Metode Pembayaran Non-Tunai (QRIS GoPay) - Ramdani, Dani; Reswanti J.P., Roro Arinda; Hamidah, Syifa Fauziah; Marquerette, Lindi Utami (Jurnal Pengabdian Tri Bhakti, 2025)
The progression of the digital era necessitates the enhancement of digital financial literacy, particularly among small-scale entrepreneurs. QRIS (Quick Response Code Indonesian Standard) has emerged as a widely adopted digital payment method across Indonesia, including among merchants within the Langlangbuana University (UNLA) environment. Nevertheless, the level of understanding and adoption of this system remains relatively low, primarily due to limited exposure to digital financial education. This program aims to increase merchants’ comprehension of non-cash transactions utilizing QRIS GoPay through an educational approach combined with direct mentoring. Employing a participatory framework, the program encompasses stages of socialization, training, and evaluation. The findings reveal that 85% of participants demonstrated an understanding of QRIS functionality post-program, and 50% successfully activated their QRIS GoPay accounts during the training sessions. These outcomes indicate the program's effectiveness in fostering digital financial literacy and advancing financial inclusion within the UNLA community